SISTEM PAKAR DIAGNOSA PENYAKIT AYAM MENGGUNAKAN PERINTAH SUARA - Bambang Yuwono (Jurusan Teknik Informatika, 2011)
This research was conducted based on the need for a tool for farmers and extension workers in diagnosing the disease in chickens. The tools in the form of an expert system which in addition to diagnosis is also able to provide medical advice. This expert system in the consultation can be run using voice commands to answer every question with a yes or no vote. The process of speech recognition using SAPI (Speech Application Programming Interface) is a tool that is used to process the analog sound is then converted to text. Inference method used is backward chaining with the model of Depth First Search. The output of this system in the form of the name of the disease and treatment suggestions.